PROSES BERPIKIR MAHASISWA DENGAN KEMAMPUAN SPATIAL INTELLEGENT TINGGI DALAM MEMECAHKAN MASALAH GEOMETRI - Murtafi’ah, Wasilatul; Masfingatin, Titin (KadikmA, 2015)
Abstract. This study aims to describe the process of thinking student of mathematics education with high spatial intellegent in solving geometry problems based steps Polya problem solving. This research is a qualitative descriptive study. The subject of this study is a second semester students of Mathematics Education IKIP PGRI MADIUN with a high degree of spatial intelligence. Data collection techniques were used that method of written test and interview-based tasks. Data analysis was conducted based on data written test and interview-based tasks. Furthermore, to obtain valid data triangulation method of writing data from and interviews. This research resulted in the description of the thought processes of students with a high level of spatial intelligence in solving geometry problems. In understanding the problem using the thought process of assimilation, in a problem-solving plan to use the thinking process is less than perfect assimilation and accommodation. In implementing the plan of solving students with high spatial intelligence using the thought process of assimilation. While in checking the breakdown of students with high spatial intelligence the process of assimilation and accommodation. Keywords: thought processes, spatial intelligence, geometry problem solving. Â